UNTENABILITY OF THE LAW OF SUPPLY - Andrey V. Bystrov (Plekhanov Russian University of Economics, 2017)
The article investigates the fundamental hypotheses of the neo-classical theory, i. e. the law of supply and the law of declining profitability. Based on the practice of real production and arguments of prominent world economists the authors come to the conclusion that in the field of the classical law of supply the hypotheses being considered have no justified proof and contradict to the realities of man-machine production. Analyzing technological foundations of the production system is one of the most interesting aspects discussed in the article. It should be pointed out that this subject is not the focus of modern economists' attention, though these aspects determine the dynamics of developing production apparatus and the level of corporate competitiveness.